Meningkatkan Kompetensi Digital Masyarakat Desa Lambangsari Berbasis Sistem Informasi Website - Nikmah; Verdi Ganda; Muhammad Allum Istifahany; Esa Meila; Krispinus Nathaniel; Muhamad Zaky; Muhammad Khoziali; Moch Alfitho; Laudza; Muhamad; Muhammad Hisyam; Ahmad; Adi Muhajirin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The Community Service Program conducted in Lambangsari Village, Tambun Selatan District, Bekasi Regency, was initiated in response to the limited availability of digital information media at the village level, which hindered the effective dissemination of public information. This program aimed to enhance community digital literacy and optimize the use of information technology through the revitalization and utilization of the village website. The implementation methods included field observation, interviews, documentation, website development, as well as community socialization and mentoring activities. Program evaluation was carried out through observation and comparison of community understanding before and after the activities. The results indicated an improvement in public awareness regarding the positive and responsible use of digital technology, along with easier access to official village information. The village website began to function as a medium for information dissemination, education, and support for public services. These findings demonstrate that the implementation of a village website is effective in increasing digital information literacy, enhancing information transparency, and supporting more modern and efficient public services at the village level.